Loss of consciousness in judo: similarities and differences between traumatic brain injury and choking techniques (shime-waza) - Lota, K. S.; Malliaropoulos, N.; Callan, M.; Ikumi, A. (The Arts and Sciences of Judo, 2023)
Loss of consciousness (LOC) is a critical event that can occur in judo as a result of both traumatic brain injury (TBI) and choking techniques (shime-waza). This research note explores the similarities and differences between these two distinct causes of LOC, in the context of judo. The aims are to further knowledge surrounding these phenomena, provide additional insight into the underlying mechanisms and emphasise the importance of safety and risk management in training and competition. Firstly, the research note explores and compares the underlying physiological mechanisms through which TBI and shime-waza can cause LOC. The short and long-term consequences of both instances, as well as the significance of repeated injuries on player health, and considerations for safety and risk management strategies in the sport suggested by governing bodies are discussed. A comprehensive understanding of the similarities and differences between LOC caused by TBI and shime-waza is vital in order to increase awareness amongst players, coaches, officials, and researchers alike. Thus, appropriate precautionary measures regarding player safety can be implemented in judo, and allow those who participate to continue enjoying the sport to its full extent.